PSIV-18 Effect of two dietary crude protein levels on finishing performance, meat quality, and genomic changes of lambs. (5th December 2019) - Shelby, Sarah; Thakali, Keshari; Wang, Yongjie; Apple, Jason; Huang, Yan
Abstract: This study investigated the effects of 2 different CP levels on the finishing performance, meat quality, and genomic changes of market lambs. Seventeen crossbred lambs were assigned randomly to low-protein (LP; 8% CP, n = 9) and high-protein (HP; 13% CP, n = 8) diets, with initial mean body weights tabulated (37.5±1.97 and 39.5±2.17 for LP and HP group), and allowed ad libitum access to diets and water in individual, indoor digestibility pens for 9 weeks. The final BW, ADFI, and ADG of the HP lambs were significantly greater (P < 0.05) than the LP lambs; however, G:F for the LP lambs was significantly greater (P < 0.05) than the HP lambs. Hot carcass weight, adjusted fat thickness, and drip loss of LM was significantly greater (P < 0.05) for the HP than LP lambs. In contrast, instrumental color values L*, a*, b*, C*, and hue angle of meat from the LP lambs scored higher (P < 0.05) than the HP lambs. Oxymyoglobin percentage from LP lambs tended greater (P < 0.10) than HP lambs. Deoxymyoglobin from HP lambs was significantly greater (P < 0.01) than LP lambs. Metmyoglobin from HP lambs was significantly greater (P < 0.01) than LP lambs. The n6:n3 of the LM from LP lambs tended to be greater than that of HP lambs (P < 0.10); conversely, the LM from HP lambs had significantly greater CLA of cis-9 trans-11 isomer (P < 0.05) than the LP lambs. According to the RNA-Seq data, genes that were highly expressed in the LP group (fold change > 3, P < 0.05) were involved in lipid metabolism (GRAMD2, PIK3R3), fatty acid composition (CHAC1), IMF content (ATXN7L1), and carcass quality traits (CCDC158). These results demonstrated that higher CP protein promotes growth performance for finishing lambs, whereas lower CP is beneficial for meat quality, especially when evaluating color characteristics in the final product.